2023
DOI: 10.1186/s43088-023-00367-8
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-22 and interleukin-33 show up-regulated levels in the serum of patients with mild/moderate Coronavirus disease 2019

Abstract: Background This study analyzed serum concentrations of interleukin (IL)-22 and IL-33 (pro-inflammatory and anti-inflammatory cytokines) in 90 patients with mild/moderate coronavirus disease 2019 (COVID-19) and 90 healthy controls. Enzyme-linked immunosorbent assay kits were used to measure IL-22 and IL-33 concentrations. Results Median (interquartile range) concentrations of IL-22 and IL-33 were significantly higher in patients than in controls (IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
1
0
0
Order By: Relevance
“…However, a non-significant number of patients in all age groups had IL-33 levels above the standard range. Similar results were observed by Majeed et al in their study [ 33 ]. IL-33, a member of the IL-1 family, is an alarmin cytokine with crucial roles in tissue homeostasis and repair, type 2 immunity, allergic and non-allergic inflammation, viral infection, and cancer [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, a non-significant number of patients in all age groups had IL-33 levels above the standard range. Similar results were observed by Majeed et al in their study [ 33 ]. IL-33, a member of the IL-1 family, is an alarmin cytokine with crucial roles in tissue homeostasis and repair, type 2 immunity, allergic and non-allergic inflammation, viral infection, and cancer [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…This study found a stepwise increase in IL-1β fold change moving from healthy controls (1.06 to mild/moderate COVID-19 patients (4.74, p<0.001) and finally to the severe disease group (13.29, p<0.001). This aligns with Paranga et al [12], Bagheri-Hosseinabadi et al [13], and Majeed et al [1], where IL-1β similarly rose with advancing COVID-19 severity compared to controls. Adnan Mezher et al, [14].…”
Section: Survival Analysessupporting
confidence: 90%
“…Aligning with Shafiek et al, IL-1β also exhibited good diagnostic accuracy (AUC 0.846). Furthermore, the extensive cytokine panel in Majeed et al [1] identified some markers comparable to our IL-8, while we found better sensitivity/specificity. Compared to Bergantini et al, [22] The IL-8 cut-off provided higher AUC (0.960 vs 0.88) and sensitivity (100% vs 66%), suggesting improved precision identifying severe presentations.…”
Section: Survival Analysessupporting
confidence: 66%
See 2 more Smart Citations